2005
DOI: 10.1111/j.1538-7836.2005.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of thrombosis in patients with acute leukemia: occurrence of thrombosis at diagnosis and during treatment

Abstract: Summary.  Background: Thromboembolism can occur during acute leukemia, especially acute lymphoid leukemia (ALL) treated with l‐asparaginase. Yet, most reports are anecdotical and scarce data are available on the risk of thrombosis in acute myeloid leukemia (AML). Objectives: To evaluate the risk of thrombosis in patients with acute leukemia. Patients and methods: Three‐hundred and seventy‐nine consecutive adult patients with newly diagnosed acute leukemia were recruited in an observational cohort study conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
170
1
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(192 citation statements)
references
References 41 publications
10
170
1
11
Order By: Relevance
“…Only two very recently published studies have dealt with the association of VTE and acute leukaemia: in an observational cohort study of 379 acute leukaemia patients, 3.4% had VTE as a presenting manifestation and further 3.2% developed VTE within 6 months after diagnosis of leukaemia (de Stefano et al, 2005). Patients with ALL receiving L-asparaginase were at particularly high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Only two very recently published studies have dealt with the association of VTE and acute leukaemia: in an observational cohort study of 379 acute leukaemia patients, 3.4% had VTE as a presenting manifestation and further 3.2% developed VTE within 6 months after diagnosis of leukaemia (de Stefano et al, 2005). Patients with ALL receiving L-asparaginase were at particularly high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Asparaginase is associated with an increased risk of vte 9,10 that is largely related to inhibition of hepatic protein synthesis, leading to decreased plasma levels of antithrombin and proteins C and S 11,12 . In all, increased age has been identified as a risk factor for vte, the incidence being 34% in adults compared with 5% in pediatric patients treated with asparaginase-containing regimens 13 .…”
Section: Introductionmentioning
confidence: 99%
“…4 In contrast, there is a correlation with certain hematology malignancies, namely, acute leukemia, primary amyloidosis, and myeloproliferative neoplasms. De Stefano et al 40 showed that the incidence of thrombosis in acute promyelocytic and lymphoblastic leukemia is 9.6% and 1.4%, respectively, at the time of presentation. More than 50% of these events involved an arterial bed.…”
mentioning
confidence: 99%